Development of Ayurveda – Tradition to trend. (2nd February 2017) - Mukherjee, Pulok K.; Harwansh, Ranjit K.; Bahadur, Shiv; Banerjee, Subhadip; Kar, Amit; Chanda, Joydeb; Biswas, Sayan; Ahmmed, Sk. Milan; Katiyar, C.K.
Abstract: Ethnopharmacological relevance: Ayurveda entails a scientific tradition of harmonious living and its origin can be traced from ancient knowledge in Rigveda and Atharvaveda . Ayurveda is a traditional healthcare system of Indian medicine since ancient times. Several Ayurvedic medicines have been exploiting for treatment and management of various diseases in human beings. The several drugs have been developed and practiced from Ayurveda since ancient time to modern practice as 'tradition to trend'. The potential of Ayurvedic medicine needs to be explored further with modern scientific validation approaches for better therapeutic leads. Aim of the study: The present study was aimed to explore the various aspects of Ayurveda and inspired drug discovery approaches for its promotion and development. Materials and methods: We have reviewed all the literature related to the history and application of Ayurvedic herbs. Various aspects for the quality control, standardization, chemo-profiling, and metabolite fingerprinting for quality evaluation of Ayurvedic drugs. The development of Ayurvedic drugs is gaining momentum with the perspectives of safety, efficacy and quality for promotion and management of human health. Scientific documentation, process validation and several others significant parameters are key points, which can ensure the quality, safety and effectiveness of Ayurvedic drugs. Results: The present review highlights on the major goal of Ayurveda and their significant role in healthcare system. Ayurveda deals with several classical formulations including arka, asavas, aristas, churna, taila, vati, gutika, bhasma etc. There are several lead molecules that have been developed from the Ayurvedic herbs, which have various significant therapeutic activities. Chemo-profiling of Ayurvedic drug is essential in order to assess the quality of products. It deals with bioactive compound quantification, spurious and allied drug determination, chromatographic fingerprinting, standardization, stability and quality consistency of Ayurvedic products. Conclusions: Scientific validation and the documentation of Ayurvedic drugs are very essential for its quality evaluation and global acceptance. Therapeutic efficacy of Ayurvedic herbs may be enhanced with high quality, which can be achieved by identity, purity, safety, drug content, physical and biological properties. Ayurvedic medicines need be explored with the modern scientific approaches for its validation. Therefore, an attempt has been made in the present review to highlight the crucial aspects that need to be considered for the promotion and development of Ayurvedic medicine. Graphical abstract: